A simple and robust quantum memristor - Li, Y; Holloway, G; Benjamin, S; Briggs, G; Baugh, J; Mol, J (2016)
Memristive systems are generalisations of memristors, which are resistors with memory. In this paper, we present a quantum description of memristive systems. Using this model we propose and experimentally demonstrate a simple and practical scheme for realising memristive systems with quantum dots. The approach harnesses a phenomenon that is commonly seen as a bane of nanoelectronics, i.e. switching of a trapped charge in the vicinity of the device. We show that quantum-dot memristive systems have hysteresis current-voltage characteristics and quantum jump induced stochastic behaviour. Realising such a quantum memristor completes the menu of components for quantum circuit design.